COVID-19. WHO CAN HELP US? - Klepikov, Igor (International Journal of Research -GRANTHAALAYAH, 2020)
The COVID-19 pandemic has disrupted the usual rhythm of our lives, becoming a surprise, a serious problem and a great challenge for all segments of society, but the prospects for overcoming this situation and returning to previous social standards remain unclear. Cautious and uncertain forecasts of specialists even for the near future and daily updates in the media of the number of infected and dead sow a sense of anxiety, and medical confessions about the lack of effective treatment create a sense of insecurity.